Drug Policy and the Public Good: a summary of the second edition. (14th August 2019) - Babor, Thomas F.; Caulkins, Jonathan; Fischer, Benedikt; Foxcroft, David; Medina‐Mora, María Elena; Obot, Isidore; Rehm, Jürgen; Reuter, Peter; Room, Robin; Rossow, Ingeborg; Strang, John
Abstract: The second edition of Drug Policy and the Public Good presents up‐to‐date evidence relating to the development of drug policy at local, national and international levels. The book explores both illicit drug use and non‐medical use of prescription medications from a public health perspective. The core of the book is a critical review of the scientific evidence in five areas of drug policy: (1) primary prevention programs in schools and other settings; (2) treatment interventions and harm reduction approaches; (3) attempts to control the supply of illicit drugs, including drug interdiction and law enforcement; (4) penal approaches, decriminalization and other alternatives; and (5) control of the legal market through prescription drug regimens. It also discusses the trend towards legalization of some psychoactive substances in some countries and the need for a new approach to drug policy that is evidence‐based, realistic and coordinated. The accumulated evidence provides important information about effective and ineffective policies. Shifting the emphasis towards a public health approach should reduce the extent of illicit drug use, prevent the escalation of new epidemics and avoid the unintended consequences arising from the marginalization of drug users through severe criminal penalties.